THE INFLUENCE OF WATER CYCLE VIDEO LEARNING MEDIA ON THE UNDERSTANDING OF GRADE V STUDENTS OF SDN TAROKAN 3 ON WATER CYCLE MATERIAL - Putri, Juita Cahyani; Santi, Novi Nitya; Sahari, Sutrisno (JURNAL EDUSCIENCE, 2023)
This research was motivated by the lack of learning media used by teachers when delivering material. The solution to overcome this problem is to use learning video media. The aims of this research are (1) To find out how the use of water cycle video learning media affects the understanding of class V students at SDN Tarokan 3 in the experimental class, (2) To find out how learning without using learning media affects the understanding of class V students at SDN Tarokan 3 in the control class , (3) To determine the difference between the use of water cycle video learning media and without the use of media on the understanding of class V students at SDN Tarokan 3 regarding the water cycle material. This research is a type of quantitative research with experimental techniques. The conclusion of this research is that the water cycle video learning media has a greater role in increasing students' understanding compared to delivering material without using learning media.Keywords: learning media, videos, water cycles, student understanding. Abstrak Penelitian ini dilatarbelakangi oleh kurangnya media pembelajaran yang digunakan guru saat meyampaikan materi.  Solusi untuk mengatasi masalah ini adalah dengan menggunakan media video pembelajaran. Tujuan penelitian ini adalah (1) Untuk mengetahui bagaimana penggunaan media pembelajaran video siklus air terhadap pemahaman siswa kelas V SDN Tarokan 3 di kelas eksperimen, (2) Untuk mengetahui bagaimana pembelajaran tanpa menggunakan media pembelajaran terhadap pemahaman siswa kelas V SDN Tarokan 3 di kelas kontrol, (3) Untuk mengetahui adanya perbedaan penggunaan media pembelajaran video siklus air dan tanpa penggunaan media terhadap pemahaman siswa kelas V SDN Tarokan 3 terhadap materi siklus air.  Penelitian ini merupakan jenis penelitian kuantitatif dengan teknik eksperimen. Simpulan penelitian ini adalah media pembelajaran video siklus air memiliki peran lebih dalam meningkatkan pemahaman siswa dibandingkan dengan penyampaian materi tanpa menggunakan media pembelajaran.Kata Kunci: media pembelajaran, video, siklus air, pemahaman siswa.